Até os ossos: escavando o último romance de Graciliano Ramos - Betella, Gabriela Kvacek [UNESP] (Universidade Federal do Paraná, 2014)
Starting from the set wherein Vidas Secas (1938) stands out, it is possible to establish parameters that make of Graciliano Ramos’ oeuvre the overcoming of realism due to the scope of representation and the quality of formal handling developed by the author, imbibed in the Brazilian and universal literary tradition, and whose result the criticism of Antonio Candido, skilful in taking into account the former critique, points out with precision. Perusing the facts that mark the creation and reception of Vidas Secas (including the production of the movie by Nelson Pereira dos Santos in 1963), the present work is a preamble for analyses that take into account the coherence of Graciliano Ramos with the absorption of expressive resources used by American and European practitioners of a literature engaged in adjusting the expression of contrasts and in reformulating the so-called regionalism

Partindo do conjunto no qual se destaca Vidas Secas (1938), é possível estabelecer parâmetros que fazem da obra de Graciliano Ramos uma superação do realismo graças ao alcance da representação e à qualidade do tratamento formal que o próprio autor, imbuído da tradição literária brasileira e universal, desejava e cujo resultado a crítica de Antonio Candido, hábil em considerar a crítica anterior, localiza com precisão. Percorrendo fatos que pontuam a criação e a recepção de Vidas Secas (incluindo a produção do filme de Nelson Pereira dos Santos, de 1963), este trabalho constitui um preâmbulo para análises que levam em conta a coerência de Graciliano Ramos com a absorção de recursos expressivos utilizados pelos praticantes americanos e europeus de uma literatura empenhada, tanto como consequência de uma atitude contra regimes de exceção quanto na sofisticação da escrita.
To the bone: digging out the last novel of Graciliano Ramos
Keywords: Graciliano Ramos; Regionalism; Literary tradition; Criticism tradition; Graciliano Ramos; Regionalismo; Tradição literária; Tradição crítica